Balloon-occluded antegrade transvenous obliteration via transjugular intrahepatic access for bleeding rectal varices - Shin, David S. (Radiol Case Rep, 2019)
Bleeding rectal varices in cirrhotic patients with portal hypertension can be difficult to treat endoscopically or surgically. Transjugular intrahepatic portosystemic shunt creation offers a minimally invasive method to effectively decompress the portal system but may be contraindicated in patients with poor hepatic reserve or hepatic encephalopathy. We present a case of a 44-year-old woman with persistent rectal variceal bleeding, who was a poor candidate for endoscopic intervention, surgery, or transjugular intrahepatic portosystemic shunt. We therefore performed balloon-occluded antegrade transvenous obliteration of the rectal varices via transjugular intrahepatic access, which effectively controlled her rectal bleeding.